Inovasi Kemasan dan Ekspansi Pemasaran Sayur Hidroponik di Blora Jawa Tengah - Lia Ika Kartikasari; Moh Faizin (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
One form of community economic empowerment is through business development carried out by small communities or better known as MSMEs (Micro, Small and Medium Enterprises). The term MSME refers to activities established by the community, both individuals and in the form of business entities. MSMEs have an important contribution to economic growth. It was proven in 2020. In that year, Indonesia experienced a crisis triggered by the covid-19 pandemic that occurred in early March 2020. At the beginning of the pandemic, MSMEs were the sector that was hardest hit. However, after that, MSMEs were able to bounce back and in fact many new MSMEs emerged because of the pressure of the situation. SMEs are able to overcome the country's economic problems. One of them is by producing goods or services for the community. Although the contribution of MSMEs cannot be underestimated, there are still obstacles to developing MSMEs. One of them is product packaging and limited marketing. micro businesses package products with relatively simple packaging without paying attention to the aesthetic aspects of packaging. So that potential consumers are less interested in buying the product, because the appearance of the outer packaging is less attractive. In addition, most micro-enterprises only offer products to the community around the business location and their friends. With the ABCD (Asset Based Community Development) approach, the authors carry out business development activities through mentoring. The strategy used for business development is through packaging innovation and marketing expansion. The results of this activity can be seen from the marketing aspect, namely product packaging design that is more attractive, has a high selling value and wider marketing.